Exploring factors affecting public acceptance towards tax Reform in Malaysia / Nur Erma Suryani Mohd Jamel ... [et al.] - Mohd Jamel, Nur Erma Suryani; Abd Hamid, Nadiah; Sanus, Soliha; Jaafar, Salmah; Ghazal, Noorlaila; Shamsuddin, Roszilah (UiTM Cawangan Johor, 2019)
Within three years, Malaysia has undergone two consumption tax reforms: Goods and Services Tax (GST) on the 1st of April 2015, and Sales and Services Tax (SST 2.0) on the 1st of September 2018. Although tax reform is important to revenue collection, public acceptance of the newly tax reform is crucial to ensure its success. Public acceptance may be affected by tax instrument employed by the new tax system. Reversal Theory was used as the underlying theory for the study. Thus, this study aims to explore factors that influence public acceptance towards tax reform in Malaysia. Semistructured interview sessions were conducted among lower and middle-income earners to obtain information on the extent of public acceptance of the consumption tax reform. From the interview sessions, three factors were identified namely monitoring roles by government agencies, effect of price of the good and tax awareness among the public. The findings are important for the government to take the initiative to improve the mechanism of the new tax reform in order to promote tax fairness among the public from different income levels. In addition, the findings are vital for the tax authority to improve their monitoring role and to rectify their administrative issues in order to efficiently implement tax reform in Malaysia.